How Do I Examine Parkinsonian Gait?. Issue 4 (11th March 2016) - Giladi, Nir; Herman, Talia
Abstract: Gait disturbances and falls are common among older adults and patients with Parkinson's disease. These symptoms curtail mobility, independence, and quality of life. This video illustrates important aspects of parkinsonian gait and highlights features that should be focused on during the clinical examination. These include walking speed, step length, step width, posture, arm swing, shuffling, foot clearance, turning abilities, and freezing of gait. We emphasize the need to distinguish between continuous and episodic walking difficulties and to incorporate walking while dual tasking into the gait assessment. We also demonstrate how to quantify the Timed up and Go test using a stopwatch and how to carry out other clinical tests that can be used to help to characterize mobility, such as the pull test and tandem stand. We show how to test for and provoke freezing of gait by guiding the patient through a series of demanding walking trajectories, turns, and using dual tasking and other relatively challenging conditions. Finally, the walking pattern of a patient with cautious gait of unknown origin (so‐called high‐level gait disorder) is shown. This case illustrates the contribution of fear of falling and the effects of hand support. In general, the video demonstrates the power of clinical observation and its utility when examining the gait of older adults and patients with Parkinson's disease.